Archaic chaperone-usher pili self-secrete into superelastic zigzag springs - Pakharukova Natalia; Malmi Henri; Tuittila Minna; Dahlberg Tobias; Ghosal Debnath; Chang Yi-Wei; Myint Si Lhyam; Paavilainen Sari; Knight Stefan David; Lamminmäki Urpo; Uhlin Bernt Eric; Andersson Magnus; et al. (Nature Portfolio, 2022)
Adhesive pili assembled through the chaperone-usher pathway are hair-like appendages that mediate host tissue colonization and biofilm formation of Gram-negative bacteria(1-3). Archaic chaperone-usher pathway pili, the most diverse and widespread chaperone-usher pathway adhesins, are promising vaccine and drug targets owing to their prevalence in the most troublesome multidrug-resistant pathogens(1,4,5). However, their architecture and assembly-secretion process remain unknown. Here, we present the cryo-electron microscopy structure of the prototypical archaic Csu pilus that mediates biofilm formation of Acinetobacter baumannii-a notorious multidrug-resistant nosocomial pathogen. In contrast to the thick helical tubes of the classical type 1 and P pili, archaic pili assemble into an ultrathin zigzag architecture secured by an elegant clinch mechanism. The molecular clinch provides the pilus with high mechanical stability as well as superelasticity, a property observed for the first time, to our knowledge, in biomolecules, while enabling a more economical and faster pilus production. Furthermore, we demonstrate that clinch formation at the cell surface drives pilus secretion through the outer membrane. These findings suggest that clinch-formation inhibitors might represent a new strategy to fight multidrug-resistant bacterial infections.